2021
DOI: 10.1109/tem.2019.2910381
|View full text |Cite
|
Sign up to set email alerts
|

Strategic Agility, Business Model Innovation, and Firm Performance: An Empirical Investigation

Abstract: Despite the robust literature on the nature of business models and their implications for firm performance, research on the organizational antecedents of business model innovations (BMIs) is still evolving. In this study, we empirically examine the extent to which firm-level strategic agility predicts the adoption of three (value creation, value capture and value proposition) types of BMIs. Furthermore, we propose that the relationship between firm-level strategic agility and BMI adoption is contingent on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
219
4
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 240 publications
(238 citation statements)
references
References 77 publications
(137 reference statements)
10
219
4
5
Order By: Relevance
“…Value creation as the main cluster is one of the core elements of BMI (Clauss, Abebe, Tangpong, & Hock, 2019). This position is also evident in the citation analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Value creation as the main cluster is one of the core elements of BMI (Clauss, Abebe, Tangpong, & Hock, 2019). This position is also evident in the citation analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Muthoni (2015) and Okotoh (2015) found that strategic agility has positive and significant effect on firm competitive capability and operational performance. Claub et al (2019) and Ravichandran (2018) established that strategic agility significantly improved overall firm performance. Furthermore, Khan, and Wisner (2019) established that strategic agility had significant impact on firm performance.…”
Section: Discussionmentioning
confidence: 99%
“…In literature on strategic agility within and outside Nigeria contexts, scholars in strategic management argued that strategic agility measures enhanced firm performance and mitigated environmental turbulence risks (Abbas & Hassan, 2017;Claub, Abebe, Tangpong, & Hock, 2019;Oyerinde, Olatunji, & Adewale, 2018). However, Arokodare and Asikhia (2020b) pointed out that most of the business firms especially organisations in the oil and gas industry in Nigeria have recorded unstable performance due to inappropriate employment of strategic agility measures as well as slow strategic response to challenges of environmental turbulence such as uncertainty, globalization, innovation, creativity, and changing customers' preferences.…”
Section: Introductionmentioning
confidence: 99%
“…C2-Q3: The Relationship between humanistic concern and Agility of Cooperative Enterprises (9) We will also send researchers to assist the coal industry in developing clean energy when needed by upstream enterprises, so as to achieve the goals of reducing costs, increasing efficiency and achieving win-win results.…”
Section: C3-q2: Relationship Between Management Style and Operationalmentioning
confidence: 99%
“…Conforto [6] proposed a complete definition of agility based on frame semantic analysis. Follow-up research as business leaders and human resources professionals realize the importance of agility, they propose the concept of strategic agility and begin to explore the in-depth relationship between strategic agility and human resources management [7] , entrepreneurial teams [8] and corporate performance [9] . Combined with the research purpose of this study and the previous domestic and foreign literature, this paper defines the agility of energy-based enterprises as the measures taken by enterprises to adapt to their survival and development under the influence of one or more influencing factors.…”
Section: Introductionmentioning
confidence: 99%